Crude dehydration at Coveñas terminal: simulation of the drainage process in the relay tank (2024)
In the formation of petroleum, water-in-crude emulsions occur due to the nature of the compounds present. However, these mostly pose complications for various hydrocarbon treatment processes and generate excessive costs. Therefore, oil dehydration is currently applied to separate water. The oil industry employs various methods, such as the use of surfactants with demulsifying properties to destabilize these emulsions. From the above, it was identified that a challenge related to the sedimentation process of free water in the compensation tank is expected to be completed in an ideal time of one day. However, in Coveñas it takes more than a day to complete the entire process. Therefore, an analysis was performed to examine in more detail different tests such as the bottle test and the Karl-Fischer water content test to evaluate the effect generated by the Tween 80 demulsifier in addition to a steady-state simulation in Aspen Hysys software, where it was obtained that in an average of 4 hours in a proportion of 50 ml of crude oil and 3 ml of surfactant agent, the height of the separated water reaches 2 ml with an efficiency that exceeds 70% separation. Although it was not possible to simulate the separation time in the relay tank, with the proposed tests it was possible to establish that the demulsifier does influence the stability of the emulsion